The handbook of experimental economics. - Kagel, John H. (John Henry), 1942-; Roth, Alvin E., 1951- (Princeton University Press, 2015)
This second volume of the Handbook covers some of the most exciting new growth areas in experimental economics, presents the latest results and experimental methods, and identifies promising new directions for future research. Featuring contributions by leading practitioners, the Handbook describes experiments in macroeconomics, charitable giving, neuroeconomics, other-regarding preferences, market design, political economy, subject population effects, gender effects, auctions, and learning and the economics of small decisions. Contributors focus on key developments and report on experiments, highlighting the dialogue between experimenters and theorists. While most of the experiments consist of laboratory studies, the book also includes several chapters that report extensively on field experiments related to the subject area studied.